765 Contextual secretion of nanoscale interleukin (IL)-12 by CAR T cells for the treatment of cancer. (9th November 2020) - Yang, Zhifen; Bobbins, Maggie; Choi, Hana; Stefanson, Ofir; Yang, Jin; Magallanes, Khristina; Wang, Bing; Qi, Lei Stanley; Marincola, Francesco
Abstract : Background: Interleukin(IL)-12 activates T cells and macrophages pivoting the switch that turns chronic into acute inflammation and results in cancer rejection. However, despite formidable antitumor effects in preclinical models, its clinical utilization is limited by severe systemic toxicity. Here, we present a conditional, antigen-dependent, non-editing CRISPR-activation (CRISPRa) circuit (RB-2-12) that purposefully induces minimally effective doses of IL-12 for autocrine activation of CAR-T. Methods: RB-2-12 is a CAR T cell engineered to express the IL-12 heterodimer via conditional transcription of its two endogenous subunits p35 and p40. The circuit includes a lentiviral constructs encoding an anti-HER2 (4D5) single chain variable fragment, with CD28 and CD3ζ co-stimulatory domains linked to a tobacco etch virus (TEV) protease and two single guide RNAs (sgRNA) targeting the promoter region for IL-12A orL-12B. A second constructs encodes linker for activation of T cells, complexed to nuclease-deactivated/dead Cas9 (dCas9)-VP64-p65-Rta transcriptional activator (VPR) via a TEV-cleavable linker (LdCV). Activation of CAR brings CAR-TEV in proximity to LdCV releasing dCas9 for nuclear localization to the regulatory regions and conditionally and reversibly induce nanoscale expression of the p70 heterodimer. RB-2-12 was compared in vitro to control (cRB-2-12, lacking the IL-12 sgRNAs). Results: RB-2-12 induced autocrine production of low concentrations of IL-12 upon exposure to HER2+ FaDu cancer cells resulting in significantly enhanced production of interferon (IFN)-γ, cytotoxic activity and proliferation (figure 1a). These effects were comparable to co-culturing conventional HER2-specific CAR-T cells with a modified FaDu cell line expressing high doses of IL-12 (figure 1b). Conclusions: We have previously shown that tandem suppression of PD-1 expression upon HER-2 CAR activation using CRISPR interference enhances anti-cancer properties of CAR-T cells in vivo against HER2-FaDu xenografts by promoting their persistence and long-term tumor colonization (companion abstract submitted to SITC annual meeting). We hypothesize that addition of a Th1 polarizing component such as IL-12 will exponentially increase the efficacy of reprogrammed CAR-T cells by combining enhancement of effector functions to cellular fitness. At the same time, the autocrine effects of nanoscale IL-12 production limit the risk of off-tumor leakage and systemic toxicity. Such cumulative synthetic biology approaches are currently investigated in vitro and in vivo model systems. Current work is testing the effectiveness of RB-2-12 in vivo against FaDu xenografts. Acknowledgements: None Trial Registration: N.A. Ethics Approval: Not Applicable Consent: Not Applicable References: None